Staying Afloat or Going Under: Mortgage Arrears in Norway’s Starter Mortgage Program - Kristin Aarland; Anna Maria Santiago (Tidsskrift for boligforskning, 2023)
Expanding access to homeownership among vulnerable families at the lower end of the income distribution has long been a cornerstone of housing policy in many countries, including Norway. Nevertheless, the precarity of maintaining a foothold on the housing ladder overexposes vulnerable families to the risk of falling behind on mortgage payments. Utilizing data for 6,991 families participating in Norway’s Starter Mortgage Program for the period between 2006 and 2015, we find that 6% of program participants experienced serious mortgage arrears during the first three years after mortgage origination. Poisson regression results suggest that the risk of falling into arrears was higher for households whose heads were native Norwegian, male, younger, sole applicants, had lower levels of education and larger families, had high LTV ratios or started with interest-only mortgages. While economic shocks increased the risk of mortgage arrears, effects varied by year of occurrence. Additionally, higher gross debt increased late mortgage payments while liquid savings fended them off. Finally, we discuss the role of municipal leniency and forbearance in keeping vulnerable homeowners afloat.